Factors associated with unprotected anal intercourse among men who have sex with men in Douala, Cameroon. Issue 2 (24th August 2009) - Henry, E; Marcellin, F; Yomb, Y; Fugon, L; Nemande, S; Gueboguo, C; Larmarange, J; Trenado, E; Eboko, F; Spire, B
Abstract : Objectives: Research on men who have sex with men (MSM) in sub-Saharan Africa was neglected for a long time. The objective of this study was to understand factors associated with unprotected anal intercourse (UAI) with male partners among a group of MSM living in the city of Douala, Cameroon. Methods: In 2008, a survey on the sexual activity and practices of MSM was set up in Douala in collaboration with a local community-based organisation. Data were collected among a convenience sample of 168 MSM during face-to-face interviews with trained interviewers. Results: A total of 142 individuals reported sexual activity during the previous 6 months, among whom 80 (57%) reported UAI with male partners. In a multivariate logistic regression model adjusted for the frequency of sexual intercourse, not having had access to prevention interventions and not knowing any HIV-infected person were both independently associated with a higher risk of UAI. Other factors associated with this higher risk included having had a stable male partnership at some point in one's life and not having been out of Douala for more than 4 weeks during the previous year. Conclusions: This community-based research is the first study of MSM in Cameroon and the HIV transmission risks they face. Results show the importance of HIV prevention interventions from peers, and underline the need to maintain efforts to develop specific interventions targeting MSM more efficiently in the African context.